The Transformation of Learning Models in Elementary Education toward Innovative Student Centered Learning in the 21st Century - Romi Laspita; Nuratna Fitri Hasanah; Fitri Andini; Nadila Putri Nassel; Afifah Rahmadani; Hastika Alwisa; Annisya Azzahra; Atika Mawaddah; Silvia Aulia; Sintia Ayu Lestari; Dinia Putri Marsha; Elsa Novi Safitri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The transformation of learning models in elementary schools is an essential effort to address the demands of twenty-first-century education, which emphasizes the development of critical thinking, creativity, collaboration, communication, and the effective use of technology in the learning process. The shift from teacher-centered learning to student-centered learning has become necessary to create more active, innovative, and meaningful learning experiences. This article aims to analyze the transformation of learning models in elementary schools in promoting innovative, student-centered learning for the twenty-first century. The study employed a library research method by reviewing relevant scholarly literature, journal articles, books, and educational policy documents. The findings indicate that the transformation of learning models can be achieved through the implementation of innovative instructional approaches, including Project-Based Learning, Problem-Based Learning, Inquiry Learning, and Discovery Learning, all of which enhance students' active engagement in the learning process. Furthermore, the integration of digital technology and the implementation of the Merdeka Curriculum support the development of flexible, creative, and learner-centered educational practices. The transformation of learning models in elementary schools has a positive impact on improving learning outcomes, fostering twenty-first-century skills, and developing students' independence and sense of responsibility. Therefore, effective and sustainable learning transformation requires teacher readiness, institutional support, and the optimal utilization of digital technology.